Fast indexing for blocked array layouts to reduce cache misses. (3rd April 2006) - Athanasaki, Evangelia; Koziris, Nectarios
Several studies have been conducted on blocked data layouts, in conjunction with loop tiling to improve locality of references. In this paper, we further reduce cache misses, restructuring the memory layout of multi-dimensional arrays, so that array elements are stored in a blocked way, exactly as they are swept by the tiled instruction stream. A straightforward way is presented to easily translate multi-dimensional indexing of arrays into their blocked memory layout using quick and simple binary-mask operations. Actual experimental results and simulations illustrate that performance is greatly improved because of the considerable reduction of cache misses.